Respuesta :
Answer: 1
Step-by-step explanation:
Just plug in -2 anywhere you see an a
[tex]f(a)=2a^3+3a^2+5\\f(-2)=2(-2)^3+3(-2)^2+5\\f(-2)=2(-8)+12+5\\f(-2)=-16+12+5\\f(-2)=1[/tex]
⊰________________________________________________________⊱
Answer [tex]\curvearrowright[/tex] [tex]\\[/tex]
f(-2)=1
Step-by-step explanation [tex]\curvearrowright[/tex]
Given,
- Original Expression = [tex]\sf{f(a)=2a^3+3a^2+5}[/tex]
To find,
- f(-2) = ??
All work is shown here. :))
[tex]\Large\begin{gathered} \boldsymbol{\sf{Plug \ in \ the \ number \ for \ a, \ which \ is \ -2 (it's \ given \ to \ us). Then}}\\ \boldsymbol{\sf{evaluate,}} \\ \curvearrowright\\\boldsymbol{\sf{Now \ substitute \ -2}} \\\curvearrowright\\\sf{2(-2)^3+3(-2)^2+5}\\\sf{2*(-8)+3*4+5}\\\sf{}-16+12+5=-4+5}\\\underline{\boxed{\sf{f(-2)=1}}}\end{gathered}[/tex]
Done !!
⊱______________________________________________________⊰
[tex]\tiny\pmb{CALLIGRAPHY}[/tex]